APPLICATION OF SWOT ANALYSIS AS A MARKETING STRATEGY IN RUMAH INDUSTRI LAJU JAYA MANDIRI - Ahmad Suhaeli; Citra Savitri; Syifa Pramudita Faddila (SEAN Institute, 2022)
Karawang is one of the industrial cities in Indonesia. As a growingindustrial city, the pace of economic growth as well as changes intechnology and information is accelerating. This has become one of thedriving factors for the creation of intense competition and forces MSMEactors to continue to innovate and design strategies to compete forconsumers and meet consumer needs and desires. In addition, theCORONAVIRUS pandemic has brought many changes to the social andeconomic situation that have a direct impact on company turnover.Research Objectives To find out what strategies the company should do inorder to optimize sales, understand changes and continue to exist in themidst of intense competition. This type of research is descriptive(qualitative). The type of data used in this study is primary data. Theresults of internal and external analysis that the company still has manyshortcomings are known in the marketing process, the Home Industrycompany, the pace of independent success is less fast in adapting to thepace of growth and changing times, as well as the lack of strategy in themarketing process in the midst of such tight competition. The results ofthe External and Internal Environmental Analysis, SWOT Analysis areknown that there are several problems and obstacles in the marketingprocess experienced by the Company, including, less massive promotion,not yet have a trademark, limited capital, less efficient production system,unstable product quality, lack of Innovation, Packing is not neat, Prices arenot competitive. Suggestions for efforts that can be made by the companyinclude making a trademark, this is very vital because it is a productidentity, passive promotion, improving the production system becauseproduct quality directly affects customer satisfaction. And reformulatepricing to be more competitive and create new innovations in order tosurvive in the competition